PEMBERIAN Spirulina sp DENGAN DOSIS BERBEDA TERHADAP KELULUSHIDUPAN DAN PERTUM¬BUHAN BENIH IKAN SEPAT SIAM (Trichogaster pectoralis REGAN) - Rosyadi Rosyadi (DINAMIKA PERTANIAN, 2012)
This experiment was conducted at the Fish Hatchery, Faculty of Agriculture, Riau Islamic University Pekanbaru during three months. The aims of this experiment were to find out the effect of doses of Spirulina sp on survival and growth of seeds of Trichogaster petroralis Regan. Twenty-days-old seed of T. petroralis Regan were used in this study. The average length and weight of fish seed were 1.2 cm and 0.072 g respectively, with initial stocking density of 5 individual/liter. A completely randomized design with three replicates was used in this experiment. Spirulina sp (in the form of powder/dry) with different doses, P1 (5%), P2 (10%), P3 (15%), and P4 (20%) per body weigh were used as treatment. The results showed that the highest weight obtained was found to be 0.625 g at treatment 10%, while the lowest weight was found to 0.452 g in treatment 20%. The seed length of T. pectoralis was approximately 1.4 cm in treatment 10%, it was longer than the length of the seed 1.3 cm at treatment 5%, 15%, and 20%. The highest survival of T. pectoralis was found to be 88.90% at treatment 10%, while the lowest survival was found at treatment 20% to be 49.33%. The growth rate of daily weight of T. pectoralis for 10% was the highest 7.86%, and the lowest was found in 20% to be 6.83%.